تأثير الرفاهية والروحانية في مكان العمل على الالتزام التنظيمي - علي عبودي، نعمة (جامعة الوادي University of Eloued, 2024)
The aim of the research is to recognize the impact of wellbeing and spirituality in the workplace and its constituent concepts on the quality of working life of workers at the General Sponsor Hospital. A cross-sectional survey of spirituality in a workplace was completed by 370 employees of the NajafIraq Health Department. The data was analyzed using SPSS22 software, identifying metadata, conducting an independent t- ‐ test, Pearson correlation coefficient, and multiple hierarchical regression. The results were: average scores for all sub-bands were average. Age, and duration of work, were positively linked, especially the harmony between workplace and individual. In the second hierarchical decline, control of general characteristics, harmony between workplace and individual, and relationship with colleagues were important factors that illustrated 59.0% of the variance. This model was found to be appropriate. We have indicated in the conclusions: effective and practical regulations and intervention programmes based on organizational support, including support to colleagues to increase the quality of working life of the Najaf Health Service workplace.
The Impact of Workplace Wellbeing and Spirituality on Regulatory Commitment Analytical study in the Najaf Governorate Health Department, Iraq
Keywords: الرفاهية; الروحانية; مكان العمل; الالتزام التنظيمي; organization mission; organizational well; leaders